The Demand for Money and Goods in the Theory of Consumer Choice with Money - Dusansky, Richard (American Economic Review, 2016)
When monetary balances are introduced into the consumer's utility function and budget constraint, the resulting demand functions for money and for the consumption goods in general do not exhibit the standard Slutsky-Hicks properties. Many researchers have studied this issue and have attempted to remedy the outcome; for example, see M. Morishima (1952), C. Lloyd (1964, 1971), J. Hadar (1965), and Dusansky-Kalman (1972, 1973). Their paramount goal has been to provide a neoclassical integration of money demand and consumer choice theory that will yield the traditional demand predictions that are the hallmark of neoclassical microeconomic theory. The most recent work on this subject is by Samuelson-Sato (1984). They convincingly demonstrate that with a weakly separable utility function it is possible to reinstate symmetry and negative semidefiniteness and to generate testable predictions. In this paper, however, I show that these predictions are not those of traditional theory but a modification of them, having alternative implications (for example, the assumption of a non-inferior good is no longer sufficient to ensure a downward-sloping own demand curve). The problem is that the weak separability assumption is not sufficient to recover the traditional properties. I present an alternative class of utility functions for which the commodity demand functions do exhibit the usual Slutsky-Hicks properties. This result also holds for money demand. I. Implications of the Sanuelson-Sato Results